Colorado Pediatric Airway Score (COPUR) as a Predictor of Intubation Difficulty in Children Aged 1-8 Years - Christopher Kapuangan; Aries Perdana; Fulki Fadhila; Andi Ade Wijaya Ramlan; Raihanita Zahra; Komang Ayu Ferdiana; Rahendra Rahendra (JAI (Jurnal Anestesiologi Indonesia))
Background: Airway management is critical in pediatric anesthesia, as failure can lead to severe complications, including cardiac arrest. Anticipating and preparing for difficult intubation is essential, particularly in children with unique anatomical and physiological characteristics. The Colorado Pediatric Airway Score (COPUR) is a predictive tool for assessing intubation difficulty in pediatric patients.